Interior Reconciliation: Adopting a Posture of Peace - Campbell, Kieran (Lumen et Vita, 2018)
Peacemaking is always complex. Too often this complexity proves so burdensome that those involved find themselves paralyzed, unable to locate an appropriate starting point for the process of reconciliation. This essay proposes that “interior reconciliation”— in which individuals address and engage the interior dissonances that expose them as both sinful and graced—provides a helpful first step in the process of “exterior reconciliation” between individuals, communities, and nations. Efforts of reconciliation, which are in every case complicated, remain unsustainable if the individuals involved are not able to reconcile themselves with themselves as such. I suggest three important movements—declaration (acknowledging sinfulness and gracefulness as realities of the human experience), detection (continually locating the presence of sin and grace), and disposal (surrendering sinfulness and offering gracefulness to God)—which, in the company of the Spirit, provide what I hope will be a useful and realistic framework for the journey of interior reconciliation.